Integration of Kejawen Moralistic Values in Javanese Traditional Houses Towards Communal Living in Malaysia - Ismail, Alice Sabrina (International Journal of Culture and Art Studies, 2025)
The migration of Javanese people from Indonesia to Malaysia from the early 14th century to the 19th century due to trading and maritime activities resulted in the integration of Kejawen values -Javanese philosophical tradition in the local Malaysian context involving language, customs, and the built environment. Even though the Kejawen influences are not directly widespread despite its Hinduism and Buddhist traditions, and given Malaysia's distinct Malay-Muslim identity, the Kejawen values still influence the Javanese community's cultural practices, particularly in local Malaysian traditional ceremonies, art, and customs. Henceforth, this study's objectives, firstly, aim to identify these Kejawen characteristics, precisely the attributes of Javanese architecture, and analyse to what extent the level of Kejawen value influences the Javanese traditional house in Johore, Malaysia, after the assimilation process with the local context. The sample of Javanese houses in the Johore state was selected because their most populated community still upholds the Kejawen values and traditions. The methodology used in this study is the qualitative descriptive method under the interpretivism paradigm, which aligns the semiotics and hermeneutics methods to understand the symbolic meaning of the architectural elements. The study findings conclude that there was an assimilation process between the authenticity of Kejawen Javanese belief values and its symbolic influence on the local Malay architecture in Malaysia, which is found in the form comprising setting and location, scale and size, façade, structure, and ornament, whilst space-making involves access, circulation, hierarchy and function of the traditional houses. In this way, the traditional Javanese house becomes a living embodiment of Kejawen values, whether in its original built form or having undergone assimilation. This contributes to transnational dimensions of Kejawen values in fulfilling Malaysia's communal life in various dimensions—social, environmental, and spiritual- to achieve better living in contemporary society.